1975
DOI: 10.1071/bi9750353
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Monotreme Proteins. VI. Amino Acid Sequence of the ß-Chain of Haemoglobin From the Platypus, Ornithorhynchus anatinus

Abstract: The amino acid sequence of the 146 residues of the p-chain of the major haemoglobin from the platypus has been determined. The soluble peptides derived from the chain by tryptic digestion were isolated by paper ionophoresis and chromatography. The amino acid sequences were determined by the dansyl-Edman procedure or by further digestion with other enzymes. The tryptic peptides were aligned by homology with other p-globins. There were 14 changes in sequence compared with echidna p-chain.The number of changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1976
1976
2008
2008

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…In the monotreme lineage, a pair of ␤-like globin genes (the 5Ј and 3Ј genes) originated via duplication of a proto ␤-globin gene sometime before the divergence of the platypus and echidna. The 3Ј ␤-like globin gene of monotremes is expressed during adulthood, because conceptual translations of the platypus and echidna genes are 100% identical to the reported ␤-chain amino acid sequences of adult hemoglobin from each of the respective species (27,28). On the basis of positional homology with other ␤-like globin genes, expression of the 5Ј ␤-like globin gene is most likely restricted to embryonic erythroid cells.…”
Section: Genomic Comparison Of the ␤-Globin Gene Clusters In Monotremesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the monotreme lineage, a pair of ␤-like globin genes (the 5Ј and 3Ј genes) originated via duplication of a proto ␤-globin gene sometime before the divergence of the platypus and echidna. The 3Ј ␤-like globin gene of monotremes is expressed during adulthood, because conceptual translations of the platypus and echidna genes are 100% identical to the reported ␤-chain amino acid sequences of adult hemoglobin from each of the respective species (27,28). On the basis of positional homology with other ␤-like globin genes, expression of the 5Ј ␤-like globin gene is most likely restricted to embryonic erythroid cells.…”
Section: Genomic Comparison Of the ␤-Globin Gene Clusters In Monotremesmentioning
confidence: 99%
“…Our analysis of genomic sequence from the platypus also revealed the presence of a duplicate pair of ␤-like globin genes that originated via duplication of a proto ␤-globin gene in the monotreme lineage. Although the 3Ј member of the duplicate gene pair encodes the ␤-chain subunit of adult hemoglobin (27,28), the 5Ј member of the duplicate gene pair has not been previously characterized. On the basis of positional homology with ␤-like globin genes of other vertebrates, expression of the 5Ј gene is expected to be restricted to embryonic erythroid cells.…”
mentioning
confidence: 99%
“…In earlier papers concerned with the amino acid sequences of the IX-and /I-globin chains of the echidna (Whittaker et al 1972; and the platypus (Whittaker andThompson 1974, 1975) attempts were made to calculate the date of divergence of the monotremes from the other mammals. The estimates differed widely for the IX-and /I-globin chains (Whittaker and Thompson 1975), although an earlier divergence of monotremes compared with marsupials seemed likely. No evidence was found to siipport the theory of Gregory (see Griffiths 1968) that the monotremes are more closely related to the marsupials.…”
Section: Introductionmentioning
confidence: 87%
“…As before, the original method of and was modified to accommodate the palaeontological estimates of the dates of divergence listed by Whittaker and Thompson (1975) or suggested by Romero-Herrera et al (1973) for the primates or other mammals, and the PAM units of Dayhoff (1972) which statistically allow for hidden mutations.…”
Section: Estimation Of Dates Of Divergencementioning
confidence: 99%
“…In an effort to understand the phylogenetic relationships of the monotremes the amino acid sequences of the f3-chain (Whittaker et al 1972) and IX-chain (Whittaker et al 1973) of echidna haemoglobin IB were determined as well as the sequences of the IX-chain (Whittaker and Thompson 1974) and f3-chain (Whittaker and Thompson 1975) of platypus haemoglobin. Calculations based on the differences in amino acid sequence of the IX-chain suggested that monotremes diverged from other mammalian groups 211 million years ago, while calculations based on the f3-chain gave 132 million years for the divergence date.…”
Section: Introductionmentioning
confidence: 99%